An investigation into the bacterial diversity associated with South African latrunculid sponges that produce bioactive secondary metabolites - Walmsley, Tara Aisling (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Algoa Bay Latrunculid sponges are well known for their production of cytotoxic pyrroloiminoquinones with speculation that these secondary metabolites may have a microbial origin. This study describes a thorough investigation into the bacterial community associated with Tsitsikamma favus, Tsitsikamma scurra a newly described Latrunculia sp. and a yellow encrusting sponge associated with T. scurra. Molecular and chemical characterisation were used in conjunction with traditional taxonomy in identification of the sponge specimens. The 28S rRNA and COX1 analysis confirmed the traditional taxonomy with T. favus and T. scurra being very closely related. Chemical analysis revealed that T. favus and T. scurra shared the discorhabdins 2,4-debromo-3-dihydrodiscorhabdin C, 7,8-dehydro-3-dihydrodiscorhabdin C and 14-bromo-1-hydroxy-discorhabdin V in common with each other and Tsitsikamma pedunculata indicating that these pyrroloiminoquinones are common to Tsitsikamma sponges in general. The bacterial community associated with T. favus was explored using 16S rRNA molecular techniques including DGGE, clonal libraries of full length 16S rRNA genes, as well as 454 pyrosequencing. DGGE analysis revealed that the bacterial community associated with T. favus appeared to be highly conserved, which was confirmed by both the clone library and 454 pyrosequencing, with the Betaproteobacteria as the most dominant class. Further exploration into T. favus, as well as T. scurra, Latrunculia sp. and the yellow encrusting sponge indicated that the bacterial populations associated with each of these sponge species were conserved and species specific. OTU analysis to the species level revealed that T. favus and T. scurra shared an abundant Spirochaete species in common while the most abundant species in the Latrunculia sp. and the yellow encrusting sponge belonged to the class Betaproteobacteria. The exclusivity of the tsitsikammamines to T. favus precipitated attempts to culture the T. favus associated bacteria, with a focus on the dominant betaproteobacterium as indicated by the 16S rRNA clone library. Actinobacteria associated with the Algoa Bay sponge specimens were also cultured and the actinobacterial isolates were sent for screening against Mycobacterium aurum with two Kocuria kristinae isolates and a Streptomyces albdioflavus isolate showing good antimycobacterial activity.
Keywords: Sponges -- South Africa -- Algoa Bay; Sponges -- Classification; Metabolites -- South Africa -- Algoa Bay; Marine metabolites -- South Africa -- Algoa Bay; PQQ (Biochemistry); Bacterial diversity